Assessing Different Ways of Calculating Income Zakat by Zakat Institution in Indonesia - Amal Aulia (Journal of Islamic and South East Asian Finance and Accounting, 2023)
This research aims to analyze the different methods for calculating income zakat in Indonesia, examine the causes and impacts, and find the most applicable method based on the Al-Quran and hadith. This study uses a qualitative approach. The population in this study includes all zakat institutions in Indonesia. This study uses 33 zakat institutions. Research data were collected from the internet (i.e., the websites of zakat institutions in Indonesia). The data analysis compares the methods and procedures for calculating zakat based on income applied by different zakat institutions. Based on the results of the study, Indonesia's 33 zakat institutions only 23 institutions that collect and distribute zakat on income, this is because there are differences in Islamic scholars' opinions on calculating zakat on income provisions. The differences are mainly based on the type of nisab used, basic needs, and debt-free status, but not the zakat rate.